(untitled) (Research, Society and Development, 2023)
Introduction: the new coronavirus pandemic has become one of the main causes of global concern. Sars-CoV-2 is a virus transmitted by droplets suspended in the air and mainly infects the respiratory tract, also causing systemic symptoms. In this scenario, the medical population is particularly important, as they are more exposed to infected patients and, therefore, have a greater risk of contamination. Objectives: to present the epidemiological profile of doctors in the state of Acre and analyze variables that may influence the risk of infection of doctors in Acre by Sars-CoV-2, as well as analyze and compare infection statistics between doctors and the general population. Methodology: this is a cross-sectional study, carried out using a self-completed questionnaire sent via social networks and email to the population of Acre doctors working in the public sector of the state of Acre. The variables were analyzed in response frequencies for age, sex, infection, training and use of PPE, in addition to being related according to interest for the study. Results and discussion: The results showed that there is a relationship between frontline work by doctors in the state of Acre and a greater risk of COVID-19 infection. But there was no significant association between infectivity and age, sex, type of care provided, level of care provided, use of specific types of PPE or number of hours worked. Conclusion: the findings of this study show the importance of training and consideration of multiple variables when working directly with patients infected with COVID-19.